ETNOMATEMATIKA RUMAH ADAT LAMPUNG LAMBAN DALOM KEBANDARAN MARGA BALAK - Arnidha, Yunni; Wahyuni, Endang; Amelia Putri, Fricilla (Jurnal Muara Pendidikan, 2024)
Ethnomathematics research conducted by several researchers has proven that various ethnic groups apply mathematical concepts to facilitate their daily activities. These findings support the idea that mathematics and culture have a close relationship. This study aims to determine the existence of ethnomathematical elements and philosophical meanings in the Lampung Lamban Traditional House. Dalom Kebandaran Marga Balak. This research uses qualitative ethnographic research. Data were collected through observation and interviews, and the validity of the data was determined by triangulating the data sources from the results of the interviews. Data validity is done by triangulating data sources from interviews. Based on the data obtained, the results show the existence of mathematical elements of flat shapes such as rectangles, isosceles triangles, equilateral triangles, right triangles, squares, rhombuses, and trapezoids. As for the philosophical meaning is that the structure of the house in the form of a stage was chosen to avoid wild animals, the roof has a philosophy of protection and guidance for the community, which ultimately results in a strong unity, and the wajik ornament reflects the principle of deliberation in deliberation. diamond ornament reflects the principle of deliberation in problem-solving.